Best Answer

x2 - x = 0 ?

simplifying to the initial equation by grouping of terms:

x(x-1) = 0

is true when x = 1 or x = 0

by the quadratic formula we can find the root (solution) of the equation as follows:

the equation can be rewritten as

(1(x2)) - (1(x)) + 0 = 0

so that we can see the form ax2 + bx +c = 0

Substituting our values for a, b and c into the formula, we get

x = (-b ± √(b2 - 4ac)) ÷ 2a

x = (-(-1) ± √(-12 - 4x1x0)) ÷ (2 x 1)

x = (-(-1) ± √(1 - 0)) ÷ 2

x = (1 ± 1) ÷ 2

x = 2 ÷ 2 = 1

OR

x = 0 ÷ 2 = 0

i.e. the roots (solution) of the equation x2 - x = 0 ? are when x = 1 or x = 0

Study guides

☆☆

Q: X squared minus 100

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x−6)(x+5)

x + 1

(x+4)(x-7)

x squared plus 5

They touch each other at (0, 100) on the x and y axis.

Related questions

x = ? 42 = x squared minus x

-22 - -22

By factoring I get x-3 divided by x+3

xsquared minus x minus 72

(x - 5)(x + 4)

(x−6)(x+5)

Sin squared, cos squared...you removed the x in the equation.

x + 1

The answer to x2 - 2x - 4y2 - 4y =(x - 2y)(x - 2y - 2)

(x+4)(x-7)

x squared plus 5

It is: (x+5)(x-8) when factored

People also asked